Gas Stress Analysis and Design of Drainage Process in Fault Broken Zone - ZHANG Yonggang, BAO Junrui (Meikuang Anquan, 2020)
According to the gas drainage problem of the fault fracture zone in 1301 working face of Licun Coal Mine, the FLAC3D Extrusion numerical analysis software was used to simulate the working face crossing fault model. The stress penetration distance between the gas stress anomaly zone and the overburden load is 20 m away from the front fault. Gas pre-dumping should be carried out within this range. Aiming at the problem of stuck and suction drilled in the gas drainage process due to the large internal stress of the fracture zone, the extraction technology of “high pressure in hole” with air compressor was proposed, and the gas pre-extraction plan was optimized, and the efficiency of gas drainage was improved.